Experimental Research on Dehydration Process and Strength of Concrete Influenced by Drying Temperature and Concrete Size. (18th May 2022) - Chen, Xiaoming; Zhang, Guohui; Zhou, Wei; Liu, Hongchuan; Yang, Shiqiang
Abstract : Moisture has a significant effect on the properties of concrete, and drying concrete in an oven is a common method to obtain specimens with different moisture content. In this paper, C30 concrete specimens with different sizes were oven-dried at constant temperatures of 60, 80, 105, 120, and 150 °C, respectively. The change of specimen mass, ultrasonic testing, and compressive and splitting tensile strength were tested before and after drying. The size effect and the size effect law (SEL) of concrete were analysed. The results indicated that the maximum drying rate and water loss ratio of the specimens with different sizes under the same drying temperature are basically the same. The larger the size, the longer the drying time. After drying, the concrete compressive and splitting tensile strength have increased to varying degrees, and the smaller the size, the greater the increase. For C30 concrete with different sizes, the drying temperature that has the minimal influence is 105 °C. The SEL was modified by introducing drying temperature, and the formulas were obtained after drying.